Magnetostatic Interaction Between Two Nanotubes During Magnetization Reversal by Vortex Domain Walls - Escrig-Murua, J; Riveros-Rodriguez, A (Institute of Electrical and Electronics Engineers Inc., 2017)
In this work, an integral expression for the magnetostatic interaction between two nanotubes during magnetization reversal by vortex domain walls has been obtained. This expression allows the calculation of the widths of the domain walls as a function of the position of the walls, the vertical separation between them, and the separation between the nanotubes. The wall width increases with radius and, as the tubes approach each other, the wall width increases more slowly than the wall width of isolated tubes. This expression allows for the study of magnetostatic interactions between magnetic nanotubes that have been proposed as an interesting alternative for applications in spintronics, where the motion of domain walls in nanotubes is expected to occur at very high velocities. © 2010-2012 IEEE.